Cadmium levels in biological samples and its effects on blood parameters of cattle in Eloor industrial area - NISHA, A R; CHANDRASEKHARAN NAIR, A M; GOPAKUMAR, N; JOY, A D (The Indian Journal of Animal Sciences, 2011)
A study was under taken to assess the impact of environmental pollution with cadmium (Cd) in cattle of Eloor industrial belt of Kerala state. The samples were estimated for cadmium content. Cd content (ppm) in blood, serum, dung, urine and milk from cattle of Alupuram, Binanipuram, Eloor south, Eloor north were significantly higher than control values. A significant reduction was noticed in total erythrocyte count, haemoglobin and packed cell volume of the animals in the affected area. Total leukocyte count, differential leucocyte count, mean corpuscular volume, mean corpuscular hemoglobin and mean corpuscular haemoglobin concentration did not show any significant difference. Total serum protein and albumin values from cattle of Alupuram, Binanipuram, Eloor south, and Eloor North were significantly lower than control values. An increase in the serum aspartate amino transferase, serum alanine amino transferase and serum alkaline phosphates were noticed in cattle from all test areas than controls.